Elderly Forgotten? Digital Exclusion in the Information Age and the Rising Grey Digital Divide - Mubarak Farooq; Suomi Reima (Sage, 2022)
Background: Information and Communication Technology (ICT) is being spread at an unprecedented rate across the globe. Yet, new research suggests that digital divide is not only continuing but also deepening at the same time. After access to basic ICT equipment, it is now the lack of skills and quality of hardware and software that leads to a continuing digital divide. Digital divide which is specifically related to elderly is known as grey digital divide. Objectives: The focus of this paper is to review and analyze recent relevant research on grey digital divide which is fast emerging as a major challenge in the era of ageing. A side objective is to raise implications for theory and practice discourses to minimize grey digital divide. Method: Literature on digital divide and grey digital divide is reviewed to gather relevant knowledge on the grey digital divide. The articles were filtered according to the relevance for grey digital divide in the present age. Literature review spanned over a 5 years’ timeline to discuss the current trends on the topic. Results: Results indicate a rising problem of ageing, mainly in developed countries. Grey digital divide constitutes a major challenge for elderly to participate and benefit from the digital revolution. Elderly face problems for basic tasks such as booking tickets or renewing bus cards to claiming old-age benefits because most of the systems are digitized. Another challenge is the social exclusion faced by elderly because they cannot connect with peers through digital networks due to lack of digital skills. This situation is also observed in developing countries, although in developing countries elderly get immediate help from family members due to the family system of joint living. Implications and future directions: A practical implication of this research can be a full-scale fieldwork in different countries of the world to further understand the grey digital divide. Joint collaboration between ICT and healthcare industry may result in revolutionizing of ergonomic ICT products and services which are elderly-friendly. It would be interesting to know how culture impacts grey digital divide across various countries.